Introducing the Asia Pacific Journal of Environment Ecology and Sustainable Development - Menon, ARR; Sathian, Brijesh; Sreekumar, VB (Asia Pacific Journal of Environment Ecology and Sustainable Development, 2014)
DOI: http://dx.doi.org/10.3126/apjeesd.v1i1.9500 Asia Pacific Journal of Environment Ecology and Sustainable Development 2013; 1:1-2